Continuous Allosteric Regulation of a Viral Packaging Motor by a Sensor that Detects the Density and Conformation of Packaged DNA - Berndsen, Zachary T. (Biophys J, 2015)
We report evidence for an unconventional type of allosteric regulation of a biomotor. We show that the genome-packaging motor of phage ϕ29 is regulated by a sensor that detects the density and conformation of the DNA packaged inside the viral capsid, and slows the motor by a mechanism distinct from the effect of a direct load force on the motor. Specifically, we show that motor-ATP interactions are regulated by a signal that is propagated allosterically from inside the viral shell to the motor mounted on the outside. This signal continuously regulates the motor speed and pausing in response to changes in either density or conformation of the packaged DNA, and slows the motor before the buildup of large forces resisting DNA confinement. Analysis of motor slipping reveals that the force resisting packaging remains low (<1 pN) until ∼70% and then rises sharply to ∼23 pN at high filling, which is a several-fold lower value than was previously estimated under the assumption that force alone slows the motor. These findings are consistent with recent studies of the stepping kinetics of the motor. The allosteric regulatory mechanism we report allows double-stranded DNA viruses to achieve rapid, high-density packing of their genomes by limiting the buildup of nonequilibrium load forces on the motor.